Angiostatic immune reaction in colorectal carcinoma: Impact on survival and perspectives for antiangiogenic therapy - Naschberger, Elisabeth; Croner, Roland S.; Merkel, Susanne; Dimmler, Arno; Tripal, Philipp; Amann, Kerstin Ute; Kremmer, Elisabeth; Brueckl, Wolfgang M.; Papadopoulos, Thomas; Hohenadl, Christine; Hohenberger, Werner; Stürzl, Michael (International Journal of Cancer, 2008)
Angiogenesis and inflammation are the 2 major stroma reactions in colorectal carcinoma (CRC). Guanylate binding protein-1 (GBP-1) is a key mediator of angiostatic effects of inflammation. Therefore, we hypothesized that GBP-1 may be a biomarker of intrinsic angiostasis associated with an improved outcome in CRC patients. GBP-1 was strongly expressed in endothelial cells and immune cells in the desmoplastic stroma of 32% of CRC as determined by immunohistochemical investigation of 388 sporadic CRC. Cancer-related 5-year survival was highly significant (p < 0.001) increased (16.2%) in patients with GBP-1-positive CRC. Multivariate analysis showed that GBP-1 is an independent prognostic factor indicating a reduction of the relative risk of cancer-related death by the half (p = 0.032). A comparative transcriptome analysis (22,215 probe sets) of GBP-1-positive (n = 12) and -negative (n = 12) tumors showed that particularly IFN-γ-induced genes including the major antiangiogenic chemokines CXCL9, CXCL10 and CXCL11 were coexpressed with GBP-1. Altogether our findings indicated that GBP-1 may be a novel biomarker and an active component of a Th-1-like angiostatic immune reaction in CRC. This reaction may affect patient's response to antiangiogenic therapy and the identification of such tumors may provide a novel criterion for patient selection. Moreover, the induction of a Th-1-like angiostatic immune reaction may be a promising approach for the clinical treatment of CRC. © 2008 Wiley-Liss, Inc.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Colorectal carcinoma; Guanylate binding protein-1; Inflammation; Interferon-γ

Anorectal gastrointestinal stromal tumors: A retrospective multicenter analysis of 15 cases emphasizing their high local recurrence rate and the need for standardized therapeutic approach - Agaimy, Abbas; Vassos, Nikolaos; Märkl, Bruno; Meidenbauer, Norbert; Köhler, Jens; Spatz, Johann; Hohenberger, Werner; Haller, Florian; Croner, Roland S.; Schneider-Stock, Regine; Matzel, Klaus (International Journal of Colorectal Disease, 2013)
Purpose: This study aims to report our multicenter experience with diagnosis, management, and prognosis of anorectal gastrointestinal stromal tumors (GIST). Patients and methods: We retrospectively reviewed cases treated and/or followed up at our institutions in the period 2000-2011. Results: Fifteen patients were identified (eight men and seven women; mean age, 55 years). Presenting symptoms were rectal/perirectal (eight), rectovaginal space (four), or retrovesical/prostatic (three) mass. Primary surgical treatment was local excision (six), deep anterior resection (eight), and palliative diagnostic excision (one). Tumor mean size was 4.8 cm. All but two cases were high risk (Miettinen and Lasota, Semin Diagn Pathol 23:70-83, 2006). R0 resection was achieved in 46 % of cases: one of six local excisions vs. five of seven deep anterior resection (16 vs. 71 %, respectively). All three cases who received total mesorectal excision had R0. Non-R0 status was mainly due to opening of tumor capsule at surgery (Rx). Seven of 14 patients (50 %) developed ≥1 pelvic local recurrences at a mean period of 48.4 months (mean follow-up, 61.6 months). Only two patients developed distant metastasis (adrenal, liver, and peritoneal). Recurrences developed after Rx (three), R1 (two), and unknown R-status (two). Successful mutational analysis in 13 patients revealed KIT mutations in all (10 exon 11, 2 exon 9, and 1 exon 13). Conclusion: Our results confirm the high local recurrence rate of anorectal GISTs (50 %) which correlates with the common practice of suboptimal oncological primary tumor resection (Rx or R1 = 7/13). This uncommon subset of GISTs needs more standardized oncological surgical approach to minimize the propensity for local disease recurrence. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2025-03-24
Keywords: Anorectal GIST; Circumferential resection margin; Margin status; Recurrence; Surgery

A novel chip-based parallel transfection assay to evaluate paracrine cell interactions - Kühn, Elisabeth; Naschberger, Elisabeth; Konrad, Andreas; Croner, Roland S.; Britzen-Laurent, Nathalie; Jochmann, Ramona; Münstedt, Helmut; Stürzl, Michael (Lab on A Chip, 2012)
Created from Fastlane, Scopus look-up

DNA stool test for colorectal cancer: hypermethylation of the secreted frizzled-related protein-1 gene. - Zhang, Wei; Bauer, Michael; Croner, Roland S.; Pelz, Jörg Otto Wilhelm; Lodygin, Dimitri; Hermeking, Heiko; Stürzl, Michael; Hohenberger, Werner; Matzel, Klaus (Diseases of the colon & rectum, 2007)
To investigate a potential mode of noninvasive screening for colorectal cancer, we evaluated the hypermethylation of the secreted frizzled-related protein-1 gene promoter in human stool DNA. In stool samples from 36 patients with colorectal neoplasia (7 adenoma, 29 colorectal cancer) and 17 healthy control subjects, isolated DNA was treated with sodium bisulfite and analyzed by methylation-specific polymerase chain reaction with primers specific for methylated or unmethylated promoter sequences of the secreted frizzled-related protein-1 gene. Hypermethylation of the secreted frizzled-related protein-1 promoter was present in the stool DNA of patients with adenoma and colorectal cancer. A sensitivity of 89 percent and specificity of 86 percent were achieved in the detection of colorectal neoplasia. The difference in hypermethylation status of the secreted frizzled-related protein-1 promoter between the patients with colorectal neoplasia and the control group was statistically highly significant (P < 0.001). Adenoma and early tumor Stage I (International Union Against Cancer) displayed both unmethylated and methylated secreted frizzled-related protein-1 promoter sequences, whereas advanced tumor stages showed only methylated secreted frizzled-related protein-1 (P = 0.05). The results indicate that this DNA stool test of hypermethylation of the secreted frizzled-related protein-1 promoter is a sensitive and specific method. It has the potential of a clinically useful test for the early detection of colorectal cancer. PURPOSE METHODS RESULTS CONCLUSIONS
Keywords: DNA methylation; Colorectal cancer; Secreted frizzled-related protein; Stool DNA test; Epigenetic marker; Cancer screening

Endothelial CCR2 signaling induced by colon carcinoma cells enables extravasation via the JAK2-Stat5 and p38MAPK pathway. - Wolf, Monika Julia; Hoos, Alexandra; Bauer, Judith; Boettcher, Steffen; Knust, Markus; Weber, Achim; Simonavicius, Nicole; Schneider, Christoph; Lang, Matthias; Stürzl, Michael; Croner, Roland S.; Konrad, Andreas; et al. (Cancer Cell, 2012)
Increased expression of the chemokine CCL2 in tumor cells correlates with enhanced metastasis, poor prognosis, and recruitment of CCR2(+)Ly6C(hi) monocytes. However, the mechanisms driving tumor cell extravasation through the endothelium remain elusive. Here, we describe CCL2 upregulation in metastatic UICC stage IV colon carcinomas and demonstrate that tumor cell-derived CCL2 activates the CCR2(+) endothelium to increase vascular permeability in vivo. CCR2 deficiency prevents colon carcinoma extravasation and metastasis. Of note, CCR2 expression on radio-resistant cells or endothelial CCR2 expression restores extravasation and metastasis in Ccr2(-/-) mice. Reduction of CCR2 expression on myeloid cells decreases but does not prevent metastasis. CCL2-induced vascular permeability and metastasis is dependent on JAK2-Stat5 and p38MAPK signaling. Our study identifies potential targets for treating CCL2-dependent metastasis.

Evaluating predictive modeling algorithms to assess patient eligibility for clinical trials from routine data - Köpcke, Felix; Lubgan, Dorota; Fietkau, Rainer; Scholler, Axel; Nau, Carla; Stürzl, Michael; Croner, Roland S.; Prokosch, Hans-Ulrich; Toddenroth, Dennis (BMC Medical Informatics and Decision Making, 2013)
Background: The necessity to translate eligibility criteria from free text into decision rules that are compatible with data from the electronic health record (EHR) constitutes the main challenge when developing and deploying clinical trial recruitment support systems. Recruitment decisions based on case-based reasoning, i.e. using past cases rather than explicit rules, could dispense with the need for translating eligibility criteria and could also be implemented largely independently from the terminology of the EHR's database. We evaluated the feasibility of predictive modeling to assess the eligibility of patients for clinical trials and report on a prototype's performance for different system configurations. Methods. The prototype worked by using existing basic patient data of manually assessed eligible and ineligible patients to induce prediction models. Performance was measured retrospectively for three clinical trials by plotting receiver operating characteristic curves and comparing the area under the curve (ROC-AUC) for different prediction algorithms, different sizes of the learning set and different numbers and aggregation levels of the patient attributes. Results: Random forests were generally among the best performing models with a maximum ROC-AUC of 0.81 (CI: 0.72-0.88) for trial A, 0.96 (CI: 0.95-0.97) for trial B and 0.99 (CI: 0.98-0.99) for trial C. The full potential of this algorithm was reached after learning from approximately 200 manually screened patients (eligible and ineligible). Neither block- nor category-level aggregation of diagnosis and procedure codes influenced the algorithms' performance substantially. Conclusions: Our results indicate that predictive modeling is a feasible approach to support patient recruitment into clinical trials. Its major advantages over the commonly applied rule-based systems are its independency from the concrete representation of eligibility criteria and EHR data and its potential for automation. © 2013 Köpcke et al.; licensee BioMed Central Ltd.
UnivIS-Import:2015-04-14:Pub.2013.tech.IMMD.infome.evalua_3

Immunohistochemical characterization of putative primary afferent (sensory) myenteric neurons in human small intestine - Brehmer, Axel; Croner, Roland; Dimmler, Arno; Papadopoulos, Thomas; Schrödl, Falk; Neuhuber, Winfried (Autonomic Neuroscience-Basic & Clinical, 2004)
Pseudouni- or multiaxonal Dogiel type II neurons are the intrinsic primary afferent (sensory) neurons (IPANs) in the guinea pig small intestine. Our aim was to decipher the chemical code of human myenteric type II neurons and to establish their putative vertical projections, i.e., from the myenteric plexus to the submucosa/mucosa. Additionally, we tried to distinguish them chemically from uniaxonal, dendritic type V neurons displaying, at first glance, similar shapes, i.e., smoothly contoured cell bodies with several long processes. Wholemount preparations of the myenteric plexus were immunohistochemically double or triple stained for neurofilaments (NF) and one or two of the following peptides: calbindin, calretinin (CR), calcitonin gene-related peptide (CGRP), somatostatin (SOM) and substance P (SP). In each triple stained wholemount three counts were conducted: (1) NF-positive pseudouni- or multiaxonal (type II) neurons including their reactivities for the above peptides, (2) uniaxonal or NF-negative neurons displaying coreactivities for the above peptides and (3) NF-reactive type V neurons taking into account their reactivities for the above markers. Additionally, type II neurons, which had an axon leading into (disrupted) interconnecting strands towards the submucosa were counted and somal areas of types II and V neurons were measured. The majority of myenteric type II neurons displayed coreactivities for SOM/CR (89.6%), SOM/SP (86.6%) and SP/CR (81.6%), respectively. A minority of type II neurons was positive for CGRP or calbindin. A small population with type III morphology (uniaxonal, long and slender dendrites) displayed the same coreactivities as type II neurons. In contrast, not one single type V neuron was coreactive for SOM/CR, SOM/SP or SP/CR. Out of 627 type II neurons counted in six wholemounts, 84 type II neurons displayed an axon which could be followed into disrupted interconnecting strands indicating a vertical projection pattern. Somal areas of type II neurons were twice as big as those of type V neurons (904±210 versus 449±110 μm). In conclusion, most human myenteric type II neurons contain SOM, SP and CR. We suggest they are the human IPANs. Type V neurons are both morphologically and chemically distinctly different from type II neurons and may represent descending interneurons. Further studies have to decipher the type-specific chemical code of type II neurons distinguishing them also from type III neurons. © 2004 Elsevier B.V. All rights reserved.
Keywords: Enteric nervous system; Gut; Innervation; Morphometry

Liver Transplant Due to Flupirtine-Induced Acute Liver Failure - Dondorf, Felix; Croner, Roland S.; Tautenhahn, Hans Michael; Felgendreff, Philipp; Ardelt, Michael; Settmacher, Utz; Rauchfuss, Falk (Experimental and Clinical Transplantation, 2020)
Objectives: Acute drug-induced liver failure is a rare indication for liver transplant. There is only one case of flupirtine-induced liver failure requiring transplant in the literature. In February 2018, the European Medicines Agency issued a withdrawal of approval for flupirtine medication in European countries as a result of the risk of acute liver failure.
CRIS-Team WoS Importer:2020-08-21

Loss of EZH2 at tumor invasive front is correlated with higher aggressiveness - Böhm, Julian; Muenzner, Julienne K.; Caliskan, Aylin; Ndreshkjana, Benardina; Erlenbach-Wunsch, Katharina; Merkel, Susanne; Croner, Roland S.; Rau, Tilman T.; Geppert, Carol-Immanuel; Hartmann, Arndt; Vial-Roehe, Adriana; Schneider-Stock, Regine (2018)
EVALuna2:205467

Molecular characterization of peripheral arterial disease in proximal extremity arteries - Croner, Roland S.; Balzer, Klaus; Schellerer, Vera; Mueller, Volker; Schlabrakowsi, Anne; Stürzl, Michael; Naschberger, Elisabeth; Lang, Werner (Journal of Surgical Research, 2012)
Purpose: Although risk factors for atherosclerosis in peripheral arterial disease (PAD) are well defined, the underlying mechanisms are poorly understood and no medication exists for causal therapy. Molecular pathways that could be targeted have not been identified so far. To address this issue, we compared the molecular profiles of healthy versus PAD proximal femoral arteries. Methods: Gene expression profiles from proximal femoral arteries of patients with PAD (Fontaine stage IIb-IV; n = 20) and femoral arteries from healthy controls (CO) (n = 3) were compared by microarray technology. We evaluated all samples by histopathology and performed microdissection on the CO tissue before molecular analysis. We analyzed genes regarding their cellular localization, molecular function, and risk factors such as hypercholesterolemia, smoking, and diabetes. We used a selected panel of genes for polymerase chain reaction validation of microarray results and compared the data with previously published studies. Results: Most genes overexpressed in PAD versus CO were located in the cytoplasm, membrane, and nucleus. Functionally, they had binding activity to nucleotides, cytoskeletal proteins, and transcription factors. They were mainly involved in immune regulation (e.g., interleukin-8, chemokine ligand 18, and allograft-inflammatory factor-1) (P < 0.01). Down-regulated genes in PAD versus CO were located in the extracellular region. They had transporter and G-protein receptor activity. They were associated with signaling, cell growth, and tissue formation (e.g., myosin VB, marker for differentiated aortic smooth muscle, myosin 11) (P < 0.01). Polymerase chain reaction successfully validated the expression of the differences among 10 selected genes (e.g., chemokine ligand 18, common leukocyte antigen, killer cell lectin-like receptor subfamily B, member 1, and interleukin-8). Conclusions: Genes enrolled in immune regulation and inflammatory response were identified as key players in PAD. Various membrane-bound molecules with binding activity are hereunder. Identification of such molecules may elucidate relevant players that act as candidates for therapeutic targets or prognostic markers in the future. © 2012 Elsevier Inc. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Artheriosclerosis; Microarray; Molecular marker; Peripheral arterial disease

Molecular mechanisms of lymphatic metastasis in solid tumors of the gastrointestinal tract. - Langheinrich, Melanie; Schellerer, Vera; Perrakis, Aristotelis; Lohmüller, Clemens; Schildberg, Claus; Naschberger, Elisabeth; Stürzl, Michael; Hohenberger, Werner; Croner, Roland S. (International Journal of Clinical and Experimental Pathology, 2012)
Tumor cell dissemination from the primary tumor site to distant organs is one of the characteristic properties of malignant tumors and represents a crucial step in the progression of disease. Although the pattern of spread may vary in different types of carcinomas, dissemination via the lymphatic system represents a common event in metastasis. The extent of lymph node metastasis is one of the major determinants for the prognosis of patients with gastrointestinal carcinomas and guides the therapeutically management. During the last decades, significant attention has been given to the molecular mechanisms that control lymphatic metastasis. The process of lymphangiogenesis has come into the focus. Lymphangiogenesis, the formation of newly lymphatics, comprises a series of complex cellular events and is controlled by a balance between pro- and anti-lymphangiogenic signals. This article will briefly describe the lymphatic system and then provide an overview of the molecular players involved in tumor lymphangiogenesis.

Notch3 signalling promotes tumour growth in colorectal cancer - Serafin, Valentina; Persano, Luca; Moserle, Lidia; Esposito, Giovanni; Ghisi, Margherita; Curtarello, Matteo; Bonanno, Laura; Masiero, Massimo; Ribatti, Domenico; Stürzl, Michael; Naschberger, Elisabeth; Croner, Roland S.; et al. (Journal of Pathology, 2011)
Increased Notch1 activity has been observed in intestinal tumours, partially accomplished by β-catenin-mediated up-regulation of the Notch ligand Jagged-1. Whether further mechanisms of Notch activation exist and other Notch receptors might be involved is unclear. Microarray data indicated that Notch3 transcript levels are significantly up-regulated in primary and metastatic CRC samples compared to normal mucosa. Moreover, Notch3 protein was expressed at strong/moderate levels by 19.7% of 158 CRC samples analysed, and at weak levels by 51.2% of the samples. Intrigued by these findings, we sought to investigate whether Notch3 modulates oncogenic features of CRC cells. By exploiting xenografts of CRC cells with different tumourigenic properties in mice, we found that the aggressive phenotype was associated with altered expression of components of the Notch pathway, including Notch3, Delta-like 4 (DLL4), and Jagged-1 ligands. Stimulation with immobilized recombinant DLL4 or transduction with DLL4-expressing vectors dramatically increased Notch3 expression in CRC cells, associated with accelerated tumour growth. Forced expression of an active form of Notch3 mirrored the effects of DLL4 stimulation and increased tumour formation. Conversely, attenuation of Notch3 levels by shRNA resulted in perturbation of the cell cycle followed by reduction in cell proliferation, clonogenic capacity, and inhibition of tumour growth. Altogether, these findings indicate that Notch3 can modulate the tumourigenic properties of CRC cells and contributes to sustained Notch activity in DLL4-expressing tumours. Copyright © 2011 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
Created from Fastlane, Scopus look-up
Keywords: angiogenesis; colorectal cancer; DLL4; Notch3

Predicting Clinical Outcomes in Colorectal Cancer Using Machine Learning - Gründner, Julian; Prokosch, Hans-Ulrich; Stürzl, Michael; Croner, Roland S.; Christoph, Jan; Toddenroth, Dennis (Studies in health technology and informatics, 2018)
Using gene markers and other patient features to predict clinical outcomes plays a vital role in enhancing clinical decision making and improving prognostic accuracy. This work uses a large set of colorectal cancer patient data to train predictive models using machine learning methods such as random forest, general linear model, and neural network for clinically relevant outcomes including disease free survival, survival, radio-chemotherapy response (RCT-R) and relapse. The most successful predictive models were created for dichotomous outcomes like relapse and RCT-R with accuracies of 0.71 and 0.70 on blinded test data respectively. The best prediction models regarding overall survival and disease-free survival had C-Index scores of 0.86 and 0.76 respectively. These models could be used in the future to aid a decision for or against chemotherapy and improve survival prognosis. We propose that future work should focus on creating reusable frameworks and infrastructure for training and delivering predictive models to physicians, so that they could be readily applied to other diseases in practice and be continuously developed integrating new data.
EVALuna2:209471

Prognostic value of β1 integrin expression in colorectal liver metastases. - Vassos, Nikolaos; Rau, Tilman; Merkel, Susanne; Feiersinger, Fabian; Geppert, Carol-Immanuel; Stürzl, Michael; Hohenberger, Werner; Croner, Roland S. (International Journal of Clinical and Experimental Pathology, 2014)
Integrins are cell surface adhesion molecules (CAM) that regulate via intercellular and cell-matrix signaling various cellular processes including wound healing, cell differentiation, division, growth, migration and metastatic dissemination. Although a correlation between carcinogenesis and changes in integrin expression, especially β1 integrin, has been reported, its role in colorectal liver metastases remains unclear. This study aimed to evaluate the expression of β1 integrin in colorectal liver metastases and to correlate the pattern of expression with clinicopathological features and to investigate the putative role of β1 integrin expression on survival of these patients. Formalin-fixed, paraffin-embedded (FFPE) tumor samples of 81 patients who were operated because of colorectal liver metastases without any neoadjuvant therapy were obtained and stained with hematoxylin and eosin (H & E). An immunohistochemical examination was performed using Dako, Peroxidase/DAB kit and a primary monoclonal β1 integrin (CD29, fibronectin receptor subunit beta; ab3167, Abcam plc). β1 integrin expression was evaluated according to the immunoreactive score of Remmele and Stegner and was related with clinicopathological features of prognostic significance and with disease-free and overall survival as well. Statistical analysis was performed using SPSS version 21.0. β1 integrin was overexpressed in tumor cells in 37 (48%) patients and in stromal cell in 27 (33%) patients. The β1 expression was not statistically correlated with clinicopathological features of the primary tumors but it was statistically correlated (p=0.03) with the histological grading of liver metastases. Kaplan-Meier survival analysis showed that there is a tendency but no statistically significant correlation in disease-free and overall survival. Considering that expression of β1 integrin in colorectal liver metastases remains controversial, specially its relation with survival of patients, we showed that the β1 expression represents a reliable prognostic factor regarding the grading of liver metastases of CRC and our findings imply that β1 integrin expression profiles may have further potential in identifying the stage of colorectal liver metastases and being a marker of prognosis in these patients. UNLABELLED METHODS RESULTS CONCLUSION